Transdiaphragmatic Intercostal Herniation following Blunt Trauma. (1st November 2012) - Sarkar, Debkumar; Warta, Melissa; Solomon, Jason
Abstract : Intercostal herniation is very rarely and sporadically reported in the literature. Intercostal hernia can occur following blunt trauma and may be associated with rib fractures. We present a case of a patient who presented with rib fractures, diaphragmatic rupture, and intrathoracic herniation of abdominal contents with subsequent herniation of both lung and abdominal contents through an intercostal defect. The patient was successfully treated with primary surgical repair of the diaphragm and intercostal hernia. The presentation, pathophysiology, and management of this rare clinical entity are discussed.